Does crossmodal attentional blink depend on spatial congruency? - Amanda J. Sinclair; Kelsey D. Croshaw; Steven L. Prime (Experimental Brain Research, 2026)

Multiple spatial scales and habitat composition drive wrasse distributions on the Great Barrier Reef - Carmen J. Ritter; Daniela M. Ceccarelli; Tane Sinclair-Taylor; Makeely I. Blandford; Andrew Cole; Murray Logan; Michael J. Emslie (Coral Reefs, 2026)

Effects of two methods of tooth resection on tooth integrity and piglet behaviour immediately before and after treatment - Anna R.L. Sinclair; Céline Tallet; Paula J. Brunton; Richard B. D’Eath; Dale A. Sandercock; Armelle Prunier (Applied Animal Behaviour Science, 2026)

Manipulating attention during eating effects food intake and medial prefrontal cortex fNIRS response in women with cognitive restraint - Eram Albajri; Hasan Ayaz; Patricia A. Shewokis; Angelo Del Parigi; Sinclair A. Smith; Jennifer J. Quinlan; Jennifer A. Nasser (Appetite, 2026)

The dolphin FRESH protocol: visual Freshwater-Related Evaluation of Skin Health in free-ranging bottlenose dolphins (Tursiops spp.) - Kristi L. Fazioli; Christina N. Toms; Ryan Takeshita; Alyssa Quackenbush; Denise Greig; Teresa Rowles; Lori Schwacke; Kathleen Colegrove; Ruth Y. Ewing; Deborah Fauquier; Denise Boyd; Aaron Bouwkamp; et al. (Frontiers in Marine Science, 2026)
Exposure to freshwater is a pressing health issue for coastal bottlenose dolphins ( Tursiops spp.). Environmental changes, including increased precipitation events and coastal infrastructure projects, are altering salinity within estuarine systems. Consequently, understanding effects of freshwater exposure on dolphins and developing tools to evaluate related health conditions is urgent. To address this need, a group of veterinarians, pathologists, epidemiologists, natural resource managers, and field biologists convened to create a protocol to visually assess freshwater-related skin lesions in free-ranging bottlenose dolphins. The Dolphin FRESH (Freshwater-Related Evaluation of Skin Health) Protocol guides users without medical backgrounds to screen and evaluate photographs by focusing on the visual identification of three primary indicators of freshwater skin disease: Overgrowth, Target-like Lesions, and Light Discoloration. By determining presence of the primary indicators and scoring associated characteristics, FRESH provides users with a relative assessment of the severity of these skin anomalies, and metrics to track progressive changes. The Scoring Rubric performed well during systematic testing, with evaluators correctly identifying freshwater cases through recognition of primary indicators and with no significant differences in total severity scores between field biologists and medical experts. FRESH is an important step in advancing knowledge on the effects of salinity fluctuations on dolphin health. When applied to photo datasets over time, this tool will enable researchers and managers to evaluate progression and regression of freshwater skin disease, occurrence and effects of multiple exposures, and the relationship between freshwater exposure skin indicators and health and survival outcomes.

Substantial impacts from the 2024 summer reverse five years of coral cover gains on the Great Barrier Reef - Daniela M. Ceccarelli; Michael J. Emslie; Murray Logan; Peran Bray; Adriana R. Campili; Neal Cantin; Andrew Cole; Michelle J. Jonker; Tane H. Sinclair‑Taylor; Briony Stephenson (Coral Reefs, 2026)
Anthropogenic climate change is fuelling repeated marine heatwaves and has triggered the fourth global mass coral bleaching event in 2023–2025, causing widespread coral mortality worldwide. Here, we document the impacts of this event on the Great Barrier Reef (GBR), where heat accumulation peaked in February–March 2024 and caused mass coral bleaching for the seventh time since 1998. We use data from the Australian Institute of Marine Science (AIMS)’s Long-Term Monitoring Program (LTMP), which during the 2024–2025 season recorded coral cover on 124 reefs distributed across the full latitudinal and longitudinal extent of the GBR. Coral cover declined to 30.0% (26.6–33.8% Credible Intervals [CIs]; a 24.8% relative decline since 2024) in the Northern GBR, to 28.6% (25.7–31.6% CIs; a 14% relative decline) in the Central GBR and to 26.9% (23.1–30.9% CIs; a 30.6% relative decline) in the Southern GBR. For the Northern and Southern GBR, this was the largest single-year decline in hard coral cover since monitoring began in 1986. Acropora corals contributed between 40 and 80% of the increases and 48–70% of the decreases in hard coral cover over the 39 monitoring years. Despite the pivotal role Acropora play in accelerating post-disturbance recovery through their rapid growth, their vulnerability to disturbance also contributes to an increasingly volatile ecosystem, where hard coral cover oscillates between record lows and record highs. Climate change is already fuelling increasingly frequent and intense heatwaves, and conditions for reef recovery will continue to deteriorate without urgent reductions of greenhouse gas emissions.

The influence of cold temperature exposure on markers of bone health in humans: A scoping review - R. Allan; H.T. Hurst; B. Akin; N. Liles; J. Dickson; J. Knill-Jones; J. Sinclair; S. Dillon; S.J. Hesketh; C. Mawhinney (Journal of Thermal Biology, 2026)

New Zealand deep-sea black coral (Antipatharia) age and growth rates: Insights into early life growth patterns - Ashley N. Davis; Dianne M. Tracey; Erik Behrens; Stewart J. Fallon; John Hellstrom; Peter Marriott; Daniel J. Sinclair (Deep Sea Research Part II: Topical Studies in Oceanography, 2026)

Novel Method for Collecting Skin Microbiome Samples From Free‐Ranging Bottlenose Dolphin - Joseph J. Hansen; Jennifer C. G. Bloodgood; Brandi Kiel Reese; Thomas B. Waltzek; Kevin Barry; Thibaut Bouveroux; Carrie Sinclair; Kuttichantran Subramaniam; Keith D. Mullin; Ruth H. Carmichael (Marine Mammal Science, 2026)
Cetacean skin microbiome samples are traditionally collected by swabbing the skin of captured animals or using skin tissue from remote biopsies. The effects of different sampling methods are not well understood, and factors such as swab type and storage methods may affect the microbiome. The objective of this study was to determine if samples collected by swabbing biopsied skin from bottlenose dolphins yield sufficient microbial DNA for gene sequencing, while testing if commonly used sampling and storage methods affect the skin microbiome. Skin swab samples were collected during remote biopsy surveys with either a nylon flocked swab and flash frozen with liquid nitrogen or with a cotton swab and stored in RNAlater. Sequencing of the V3–V4 region of the 16S rRNA gene revealed swabs from dolphin skin biopsies yielded sufficient DNA to characterize the microbiome. We found no significant difference between the two sampling and storage methods tested, suggesting that studies using different techniques may be comparable. This work also demonstrates a novel technique to collect samples for interpretation of the skin microbiome of free‐ranging animals. Benefits of this method are that it can be done without capture and preserves valuable and typically scarce biopsy skin samples for other analyses.

Anthropogenic climate change causes substantial loss of coral on the northern Great Barrier Reef during the 2024 bleaching event - Michael J. Emslie; Daniela M. Ceccarelli; Murray Logan; Makeely I. Blandford; Peran Bray; Adriana R. Campili; Neal Cantin; Severine Choukroun; Andrew Cole; Michelle J. Jonker; Clothilde Langlais; Marji Puotinen; et al. (Coral Reefs, 2025)

Evaluating the occurrence of veterinary medicines at farm scale and the efficacy of current groundwater modelling - John Nightingale; Laura Carter; Chris J. Sinclair; Philip Rooney; Stephen Jones; Paul Kay (Science of The Total Environment, 2025)

The discovery of a genetically distinct subpopulation of Haast tokoeka (Southern brown kiwi, Apteryx australis ‘Haast’) - Talia Brav-Cubitt; Heath M. Sinclair; Hugh A. Robertson; Andrew J. Veale (Conservation Genetics, 2025)
The Haast tokoeka ( Apteryx australis ‘Haast’) is a threatened evolutionarily significant unit (ESU) of tokoeka or southern brown kiwi in Aotearoa New Zealand. In this study, we investigated the genetic relationships of a small newly discovered population of tokoeka located at Junction Hill near Haast, which is geographically isolated from other tokoeka populations. Using pin feathers collected from five individuals at Junction Hill, we analysed 15 microsatellite loci and 1283 base pairs from two mitochondrial DNA loci (control region and cytochrome b ( Cytb )) to compare our results with those previously generated for Haast ( n = 49), northern Fiordland ( n = 7), southern Fiordland ( n = 4), and Rakiura ( n = 12) tokoeka. Our results show that the Junction Hill individuals are Haast tokoeka, but display genetic differentiation in Principle Component Analysis (PCA) and genetic assignment plots from the nearest Haast tokoeka population 18 km away in the Upper Arawhata Valley. The five Junction Hill individuals all possess a unique mitochondrial DNA haplotype that has not been observed previously. The mean allelic richness of the Junction Hill population (1.82) was slightly lower compared to the main Haast population (2.13). The presence of the Junction Hill population provides both numerical and range increases for the Haast tokoeka, and potentially contributes valuable new genetic diversity to the taxon. Further monitoring and conservation actions, such as increased pest control and translocations, may be necessary to ensure the preservation of this population and its unique genetic traits.

Fission‐Fusion Group Dynamics and Cooperative Hunting Stabilise Social Carnivore Populations - J. M. Fryxell; S. Mduma; J. Masoy; J. Grant C. Hopcraft; A. R. E. Sinclair; R. Dejeante; C. Packer (Ecology Letters, 2025)
Theory suggests that large social groups of carnivores should be unsustainable, due to reduced foraging efficiency because of overlapping perception radii. Using Serengeti lions as a case study, we apply behaviourally based foraging models to show that fragmentation of social groups into smaller subgroups or mutual cooperation during hunting are both plausible hypothetical mechanisms capable of sustaining larger lion prides. Data from the Serengeti ecosystem demonstrate that lion prides typically fragment into small hunting groups that are well approximated by an exponential distribution of group sizes typical of fission‐fusion social systems. A model linking fission‐fusion group dynamics with predator–prey interaction predicts both the surprising degree of population stability of the Serengeti lions as well as the long‐term persistence of large prides. There is little evidence, however, that Serengeti lions cooperate during hunting except when they hunt Cape buffalo, so fission‐fusion is apparently the dominant stabilising process in Serengeti.

Effects of acclimation on the cold tolerance of the pepper weevil - D. Catalina Fernández; Sherah L. VanLaerhoven; Brent J. Sinclair; Roselyne M. Labbé (Journal of Pest Science, 2025)
The pepper weevil, Anthonomus eugenii , is a subtropical pest of pepper plants that appears to be expanding its geographic range as evidenced by its increasing occurrence and persistence in field and greenhouse pepper crops in temperate areas. Here, we investigated the cold tolerance of A. eugenii and its potential for winter survival in temperate areas by comparing non-acclimated (24 °C) and cold acclimated (10 °C) adults and larvae for their cold tolerance strategy, supercooling points, and lower lethal thermal limits. Acclimated larvae were treated with silver iodide to assess their survival in the presence of an ice nucleator. Survival of non-acclimated adults was measured following exposure to 0 °C for an extended period. We also tested whether non-acclimated adults and larvae could survive winter at three outdoor sites in southwestern Ontario (agricultural field, adjacent to unheated building, and inside an unheated building). Adults and larvae died at freezing and even pre-freezing temperatures. Acclimation improved adult cold tolerance, decreasing the LT 50 by 3 °C, with half of the non-acclimated adults surviving around 6 days at 0 °C. External inoculation increased larval supercooling points (SCPs), but did not improve cold tolerance. In winter field studies, survival was evident only in the first month, but no insect survived afterwards at any of the overwintering sites. We conclude that A. eugenii is chill-susceptible, and winter temperatures will restrict outdoor establishment in temperate areas, but that high winter temperatures in empty greenhouses encourage indoor establishment.

Factor analysis of multimodal MRI, biofluid, and vascular biomarkers reveals latent constructs of brain health - Ella Rowsthorn; Ming Ann Sim; William T. O’Brien; Stuart J. McDonald; Katherine Franks; Benjamin Sinclair; Trevor T.-J. Chong; Stephanie Yiallourou; Marina Cavuoto; Lucy Vivash; Terence J. O’Brien; Xingfeng Shao; et al. (GeroScience, 2025)
Individual imaging and fluid biomarkers provide insights into specific components of brain health, but integrated multimodal approaches are necessary to capture the complex, interrelated biological systems that contribute to brain homeostasis and neurodegenerative disease. Using data from the Brain and Cognitive Health (BACH) cohort study ( N = 127; mean age = 67 years, 68% women), we performed an exploratory factor analysis to identify latent constructs of brain health. We included multimodal neurovascular imaging markers, brain atrophy metrics, plasma Alzheimer’s disease (AD) biomarkers, and cardiovascular risk factors. Five constructs emerged: “Brain & Vascular Health” (greater hippocampal volume, basal ganglia enlarged perivascular spaces (ePVS), cerebral blood flow, and HDL cholesterol; lower ventricle volume and BMI), “Structural Integrity” (greater cortical thickness, fractional anisotropy, and basal ganglia ePVS), “White Matter (WM) Fluid Dysregulation” (greater WM ePVS and Free Water), “AD Biomarkers” (higher phosphorylated tau [pTau]181 and pTau217; lower amyloid-beta 42/40 ratio), and “Neuronal Injury” (higher glial fibrillary acidic protein and neurofilament light chain). All constructs were associated with age (β = - 0.70–0.39, p ≤ 0.014), except for WM Fluid Dysregulation ( p > 0.05). Brain and Vascular Health and Structural Integrity (partial r = 0.305, p < 0.001) and AD biomarkers and neuronal injury (partial r = 0.248, p = 0.005) were positively correlated. Only Brain and Vascular Health was associated with global cognition (β = 0.27, SE = 0.13, p = 0.043). These findings provide a data-driven framework for examining distinct constructs underlying vascular health, fluid regulation, and neurodegenerative pathology. We demonstrate the utility of using multiple biomarkers to probe these biological systems, paving the way for future research to explore how these systems change across diverse neurodegenerative conditions. Graphical abstract

Distinct neural networks of emotional valence and uncertainty in the human amygdala underlying different mental disorders - Shitong Xiang; Chao Xie; Xiao Xiao; Tobias Banaschewski; Gareth J. Barker; Arun L.W. Bokde; Herta Flor; Antoine Grigis; Hugh Garavan; Penny Gowland; Andreas Heinz; Rüdiger Brühl; et al. (Science Bulletin, 2025)

Forever chemicals don't make hero mutant ninja turtles: Elevated PFAS levels linked to unusual scute development in newly emerged freshwater turtle hatchlings (Emydura macquarii macquarii) and a reduction in turtle populations - David J. Beale; Duncan Limpus; Georgia Sinclair; Utpal Bose; Nicholas Bourne; Sally Stockwell; Damian C. Lettoof; Rohan Shah; Thao V. Nguyen; Viviana Gonzalez-Astudillo; Christoph Braun; Albert Myburgh; et al. (Science of The Total Environment, 2024)

A dance fly (Empididae: Hilarempis Bezzi) from the Foulden Maar Fossil-Lagerstätte (Early Miocene, New Zealand) - Uwe Kaulfuss; Bradley J. Sinclair (Palaeobiodiversity and Palaeoenvironments, 2024)
New Zealand has a diverse and highly endemic fauna of dance flies (Empididae) with much of its diversity found in the tribe Hilarini. Here we report the first fossil of a dance fly from New Zealand from lacustrine diatomites of the earliest Miocene Foulden Maar Fossil-Lagerstätte in Otago. Hilarempis otagoensis sp. nov. is described from a single male specimen and assigned to the tribe Hilarini based on characters of the wing venation. This new species represents the first fossil record of the predominantly southern temperate genus Hilarempis Bezzi and the second fossil record of the subfamily Empidinae from the Southern Hemisphere. The articulated preservation suggests that Hilarempis otagoensis sp. nov. lived among riparian vegetation on the shore of the Foulden Maar palaeolake and probably drowned while skimming the water surface in search for prey or nuptial gifts.

Ecological but Not Biological Traits of European Riverine Invertebrates Respond Consistently to Anthropogenic Impacts - James S. Sinclair; Rachel Stubbington; Ralf B. Schäfer; Libuše Barešová; Núria Bonada; Zoltán Csabai; J. Iwan Jones; Aitor Larrañaga; John F. Murphy; Petr Pařil; Marek Polášek; Jes J. Rasmussen; et al. (Global Ecology and Biogeography, 2024)
Aim To determine which riverine invertebrate traits respond consistently to anthropogenic impacts across multiple biogeographic regions. Location Europe. Time Period 1981–2021. Major Taxa Studied Riverine invertebrates. Methods We compiled a database of riverine invertebrate community time series for 673 sites across six European countries spanning six freshwater ecoregions. We compared trait responses to anthropogenic impacts (quantified as changes in ‘ecological quality’) among regions for seven ‘ecological’ traits, which reflect habitat preferences, and nine ‘biological’ traits (e.g., morphology or life history), which represent taxon‐specific attributes that can influence ecosystem processes. Results Four ecological traits (current, microhabitat, salinity and trophic preferences) and one biological trait (dispersal mode) responded consistently across regions. These responses were primarily driven by spatial differences among poorer to better quality sites. Responses to temporal changes in quality were comparable but less pronounced. Main Conclusions Consistent responses to anthropogenic impacts across multiple ecological traits indicate these traits may improve broader scale measurements, comparisons and predictions of community responses. However, we could not use ecological traits to identify the actions of specific stressors because multiple traits always responded as a group. Inconsistent responses across almost all biological traits indicated that these traits may be less predictive of impacts across regions. Predictions of how biological traits, and associated ecosystem processes, respond to anthropogenic impacts may be most effective at regional scales where responses are more consistent.

Spatial Variation in Upper Limits of Coral Cover on the Great Barrier Reef - Mariana Álvarez‐Noriega; Juan C. Ortiz; Daniela M. Ceccarelli; Michael J. Emslie; Katharina E. Fabricius; Michelle J. Jonker; Marji Puotinen; Barbara J. Robson; Chris M. Roelfsema; Tane H. Sinclair‐Taylor; Renata Ferrari (Global Ecology and Biogeography, 2024)
Aim Identifying the maximum coral cover that a coral community can sustain (i.e., its ‘upper limit’) is important for predicting community dynamics and improving management strategies. Here, we quantify the relationship between estimated upper limits and key environmental factors on coral reefs: hard substrate availability, temperature and water clarity. Location Great Barrier Reef (GBR), Australia (over 1400 km). Time Period 1990 to 2022. Major Taxa Studied Scleractinian corals. Methods We used 32 years of data on coral cover around reef perimeters. Each reef was divided into four wave‐exposure habitats depending on prevailing wind conditions. For each site, we determined if hard coral cover had reached a plateau or upper limit. Next, we extracted existing estimates of hard substrate availability, modelled water temperature and Secchi depth. Then, we quantified the relationship between these environmental variables and the upper limits. Results We found varying upper limits across the GBR, with a median of 33% coral cover and only 17% of the estimated upper limits exceeded 50% coral cover. Upper limits increased towards the southern reefs. Our results show that upper limits increased with increasing hard substrate availability and decreased with temperature and, to a lesser extent, with water clarity. Main Conclusions The upper limits estimated in this study are much lower than what is commonly assumed when modelling ecological dynamics, most likely resulting in predicted recovery rates being inappropriately high. Although hard substrate ultimately restricted upper limits, there are mechanisms constraining the proportion of hard substrate that is covered by hard corals. The negative relationship between temperature and upper limits cannot be explained by changes in macroalgal abundance but may be related to changes in species composition. The quantitative relationships between the upper limits of coral cover and environmental variables will provide critical information to prioritise sites for management interventions.

Lessons learned on the feasibility of coastal wetland restoration for blue carbon and co-benefits in Australia - Valerie Hagger; Phoebe Stewart-Sinclair; Renee Anne Rossini; Maria Fernanda Adame; William Glamore; Paul Lavery; Nathan J. Waltham; Catherine E. Lovelock (Journal of Environmental Management, 2024)

Changing dynamics of Great Barrier Reef hard coral cover in the Anthropocene - Michael J. Emslie; Daniela M. Ceccarelli; Murray Logan; Makeely I. Blandford; Peran Bray; Adriana Campili; Michelle J. Jonker; Joshua G. Parker; Tara Prenzlau; Tane H. Sinclair-Taylor (Coral Reefs, 2024)

Enhanced antimicrobial efficacy and energy efficiency of low irradiance 405-nm light for bacterial decontamination - Lucy G. Sinclair; John G. Anderson; Scott J. MacGregor; Michelle Maclean (Archives of Microbiology, 2024)
Due to its increased safety over ultraviolet light, there is interest in the development of antimicrobial violet-blue light technologies for infection control applications. To ensure compatibility with exposed materials and tissue, the light irradiances and dose regimes used must be suitable for the target application. This study investigates the antimicrobial dose responses and germicidal efficiency of 405 nm violet-blue light when applied at a range of irradiance levels, for inactivation of surface-seeded and suspended bacteria. Bacteria were seeded onto agar surfaces (10 1 –10 8 CFUplate −1 ) or suspended in PBS (10 3 –10 9 CFUmL −1 ) and exposed to increasing doses of 405-nm light (≤ 288 Jcm −2 ) using various irradiances (0.5–150 mWcm −2 ), with susceptibility at equivalent light doses compared. Bacterial reductions ≥ 96% were demonstrated in all cases for lower irradiance (≤ 5 mWcm −2 ) exposures. Comparisons indicated, on a per unit dose basis, that significantly lower doses were required for significant reductions of all species when exposed at lower irradiances: 3–30 Jcm −2 /0.5 mWcm −2 compared to 9–75 Jcm −2 /50 mWcm −2 for low cell density (10 2 CFUplate −1 ) surface exposures and 22.5 Jcm −2 /5 mWcm −2 compared to 67.5 Jcm −2 /150 mWcm −2 for low density (10 3 CFUmL −1 ) liquid exposures (P ≤ 0.05). Similar patterns were observed at higher densities, excluding S. aureus exposed at 10 9 CFUmL −1 , suggesting bacterial density at predictable levels has minimal influence on decontamination efficacy. This study provides fundamental evidence of the greater energy efficacy of 405-nm light for inactivation of clinically-significant pathogens when lower irradiances are employed, further supporting its relevance for practical decontamination applications.

Characterising differences between self-reported and wastewater-identified drug use at two consecutive years of an Australian music festival - Cheneal Puljević; Benjamin Tscharke; Ellen Leslie Wessel; Cameron Francis; Rory Verhagen; Jake W. O'Brien; Richard Bade; Dhayaalini Nadarajan; Fiona Measham; M.J. Stowe; Timothy Piatkowski; Jason Ferris; et al. (Science of The Total Environment, 2024)

Enabling coastal blue carbon in Aotearoa New Zealand: opportunities and challenges - Phoebe J. Stewart-Sinclair; Richard H. Bulmer; Elizabeth Macpherson; Carolyn J. Lundquist (Frontiers in Marine Science, 2024)
Blue carbon is the carbon sequestered by coastal and marine habitats such as mangroves, saltmarsh, and seagrasses. The carbon sequestration service provided by these habitats could help to mitigate climate change by reducing greenhouse gas (GHG) emissions, as well as providing other important ecosystem services. Restoration of coastal habitats for the purpose of sequestering blue carbon can generate carbon credits, potentially offsetting the costs of restoration and any lost revenue for landowners. Coastal blue carbon projects have been successfully implemented overseas, but a blue carbon market has not yet been established in Aotearoa New Zealand (ANZ). Here we identify key data gaps that will be necessary to fill to develop a blue carbon market in ANZ. Calculation of carbon abatement through development of a standardised method is the first step and will allow economic assessment of potential restoration sites. Economic assessment will determine if the carbon credits generated will cover restoration costs and lost revenue from restored lands. Once economically feasible potential restoration sites have been identified, prioritisation of sites could be determined by the value of co-benefits produced (i.e., biodiversity). There are also legal uncertainties in ANZ and ownership of the foreshore has been a contentious topic. Current legislation provides that neither the Crown nor any other person owns or can own the common marine and coastal area, although Māori may apply for recognition of customary rights, interests, and title in the area. The legal status of property rights will have significant implications for privately owned land, as it is unclear whether land will be considered foreshore when inundated in future with sea level rise. Here, we discuss further policy enablers including the role of government and the insurance industry that could encourage uptake of carbon projects by private landowners. Filling these gaps in market assessments and recognising the key role of Indigenous owners and customary rights holders to coastal land can facilitate operationalising of coastal blue carbon opportunities in Aotearoa New Zealand.

First phylogenetic analysis of the Nearctic madicolous midges of the genus Androprosopa Mik (Diptera: Thaumaleidae) - Robert J. Pivar; John K. Moulton; Bradley J. Sinclair (Molecular Phylogenetics and Evolution, 2023)

Measuring Food Security among American Indian and Alaska Native Adults: Validity Evidence Supports the Use of the US Department of Agriculture Module - Cassandra J. Nguyen; Brian F. French; Tara L. Maudrie; Gary L. Ferguson; Valarie Blue Bird Jernigan; Ka`imi A. Sinclair (Journal of the Academy of Nutrition and Dietetics, 2023)

The imperative of arachidonic acid in early human development - Michael A. Crawford; Andrew J. Sinclair; Barbara Hall; Enitan Ogundipe; Yiqun Wang; Dimitrios Bitsanis; Ovrang B. Djahanbakhch; Laurence Harbige; Kebreab Ghebremeskel; Ivan Golfetto; Therishnee Moodley; Ahmed Hassam; et al. (Progress in Lipid Research, 2023)

Polanyi adsorption potential theory for estimating PFAS treatment with granular activated carbon - Jonathan B. Burkhardt; Adam Cadwallader; Jonathan G. Pressman; Matthew L. Magnuson; Antony J. Williams; Gabriel Sinclair; Thomas F. Speth (Journal of Water Process Engineering, 2023)

Deficiency of the mitochondrial ribosomal subunit, MRPL50, causes autosomal recessive syndromic premature ovarian insufficiency - Shabnam Bakhshalizadeh; Daniella H. Hock; Nicole A. Siddall; Brianna L. Kline; Rajini Sreenivasan; Katrina M. Bell; Franca Casagranda; Sadishkumar Kamalanathan; Jayaprakash Sahoo; Niya Narayanan; Dukhabandhu Naik; Varun Suryadevara; et al. (Human Genetics, 2023)
Premature ovarian insufficiency (POI) is a common cause of infertility in women, characterised by amenorrhea and elevated FSH under the age of 40 years. In some cases, POI is syndromic in association with other features such as sensorineural hearing loss in Perrault syndrome. POI is a heterogeneous disease with over 80 causative genes known so far; however, these explain only a minority of cases. Using whole-exome sequencing (WES), we identified a MRPL50 homozygous missense variant (c.335T > A; p.Val112Asp) shared by twin sisters presenting with POI, bilateral high-frequency sensorineural hearing loss, kidney and heart dysfunction. MRPL50 encodes a component of the large subunit of the mitochondrial ribosome. Using quantitative proteomics and western blot analysis on patient fibroblasts, we demonstrated a loss of MRPL50 protein and an associated destabilisation of the large subunit of the mitochondrial ribosome whilst the small subunit was preserved. The mitochondrial ribosome is responsible for the translation of subunits of the mitochondrial oxidative phosphorylation machinery, and we found patient fibroblasts have a mild but significant decrease in the abundance of mitochondrial complex I. These data support a biochemical phenotype associated with MRPL50 variants. We validated the association of MRPL50 with the clinical phenotype by knockdown/knockout of mRpL50 in Drosophila , which resulted abnormal ovarian development. In conclusion, we have shown that a MRPL50 missense variant destabilises the mitochondrial ribosome, leading to oxidative phosphorylation deficiency and syndromic POI, highlighting the importance of mitochondrial support in ovarian development and function.

Influence of manure application method on veterinary medicine losses to water - John Nightingale; Laura Carter; Chris J. Sinclair; Phil Rooney; Paul Kay (Journal of Environmental Management, 2023)

A retrospective analysis of mid-infrared observations of the Comet D/Shoemaker-Levy 9 and Wesley impacts on Jupiter - J.A. Sinclair; C.M. Lisse; G.S. Orton; M. Krishnamoorthy; L.N. Fletcher; J. Hora; C. Palotai; T. Hayward (Icarus, 2023)

Targeted quantitation of furan fatty acids in edible oils by gas chromatography/triple quadrupole tandem mass spectrometry (GC-TQ/MS) - Long Xu; Hao Cheng; Marco Müller; Andrew J. Sinclair; Weifei Wang; Xuhua Guo; Walter Vetter; Yonghua Wang (Food Chemistry, 2023)

Saturn’s atmospheric response to the large influx of ring material inferred from Cassini INMS measurements - Julianne I. Moses; Zarah L. Brown; Tommi T. Koskinen; Leigh N. Fletcher; Joseph Serigano; Sandrine Guerlet; Luke Moore; J. Hunter Waite; Lotfi Ben-Jaffel; Marina Galand; Joshua M. Chadney; Sarah M. Hörst; et al. (Icarus, 2023)

Are stormwater detention ponds protecting urban aquatic ecosystems? a case study using depressional wetlands - Kayla M. Hess; James S. Sinclair; Alexander J. Reisinger; Eban Z. Bean; Basil V Iannone III (Urban Ecosystems, 2022)

Dual effects of insulin resistance on mortality and function in non-diabetic older adults: findings from the Toledo Study of Healthy Aging - Leocadio Rodríguez-Mañas; Javier Angulo; José A. Carnicero; Mariam El Assar; Francisco J. García-García; Alan J. Sinclair (GeroScience, 2022)

A recessive variant in TFAM causes mtDNA depletion associated with primary ovarian insufficiency, seizures, intellectual disability and hearing loss - Farid Ullah; Waqar Rauf; Kamal Khan; Sheraz Khan; Katrina M. Bell; Vanessa Cristina de Oliveira; Muhammad Tariq; Shabnam Bakhshalizadeh; Philippe Touraine; Nicholas Katsanis; Andrew Sinclair; Sijie He; et al. (Human Genetics, 2021)

Effects of a physical activity intervention on brain atrophy in older adults at risk of dementia: a randomized controlled trial - Benjamin Sinclair; Chris Steward; Vijay Venkatraman; Rowa Aljondi; Kay L. Cox; Kathryn A. Ellis; David Ames; Colin L. Masters; Pramit M. Phal; Matthew J. Sharman; Elizabeth V. Cyarto; Michelle M. Y. Lai; et al. (Brain Imaging and Behavior, 2021)

Longitudinal changes of focal cortical glucose hypometabolism in adults with chronic drug resistant temporal lobe epilepsy - Catherine Sharpe; Benjamin Sinclair; Patrick Kwan; Rodney J. Hicks; Terence J. O’Brien; Lucy Vivash (Brain Imaging and Behavior, 2021)

Guiding principles for rewilding - Steve Carver; Ian Convery; Sally Hawkins; Rene Beyers; Adam Eagle; Zoltan Kun; Erwin Van Maanen; Yue Cao; Mark Fisher; Stephen R. Edwards; Cara Nelson; George D. Gann; et al. (Conservation Biology, 2021)
There has been much recent interest in the concept of rewilding as a tool for nature conservation, but also confusion over the idea, which has limited its utility. We developed a unifying definition and 10 guiding principles for rewilding through a survey of 59 rewilding experts, a summary of key organizations’ rewilding visions, and workshops involving over 100 participants from around the world. The guiding principles convey that rewilding exits on a continuum of scale, connectivity, and level of human influence and aims to restore ecosystem structure and functions to achieve a self‐sustaining autonomous nature. These principles clarify the concept of rewilding and improve its effectiveness as a tool to achieve global conservation targets, including those of the UN Decade on Ecosystem Restoration and post‐2020 Global Biodiversity Framework. Finally, we suggest differences in rewilding perspectives lie largely in the extent to which it is seen as achievable and in specific interventions. An understanding of the context of rewilding projects is the key to success, and careful site‐specific interpretations will help achieve the aims of rewilding.

Spatial cost–benefit analysis of blue restoration and factors driving net benefits globally - Phoebe J. Stewart‐Sinclair; Carissa J. Klein; Ian J. Bateman; Catherine E. Lovelock (Conservation Biology, 2021)
Marine coastal ecosystems, commonly referred to as blue ecosystems, provide valuable services to society but are under increasing threat worldwide due to a variety of drivers, including eutrophication, development, land‐use change, land reclamation, and climate change. Ecological restoration is sometimes necessary to facilitate recovery in coastal ecosystems. Blue restoration (i.e., in marine coastal systems) is a developing field, and projects to date have been small scale and expensive, leading to the perception that restoration may not be economically viable. We conducted a global cost–benefit analysis to determine the net benefits of restoring coral reef, mangrove, saltmarsh, and seagrass ecosystems, where the benefit is defined as the monetary value of ecosystem services. We estimated costs from published restoration case studies and used an adjusted‐value‐transfer method to assign benefit values to these case studies. Benefit values were estimated as the monetary value provided by ecosystem services of the restored habitats. Benefits outweighed costs (i.e., there were positive net benefits) for restoration of all blue ecosystems. Mean benefit:cost ratios for ecosystem restoration were eight to 10 times higher than prior studies of coral reef and seagrass restoration, most likely due to the more recent lower cost estimates we used. Among ecosystems, saltmarsh had the greatest net benefits followed by mangrove; coral reef and seagrass ecosystems had lower net benefits. In general, restoration in nations with middle incomes had higher (eight times higher in coral reefs and 40 times higher in mangroves) net benefits than those with high incomes. Within an ecosystem type, net benefit varied with restoration technique (coral reef and saltmarsh), ecosystem service produced (mangrove and saltmarsh), and project duration (seagrass). These results challenge the perceptions of the low economic viability of blue restoration and should encourage further targeted investment in this field.

Vegetation management and benthic macroinvertebrate communities in urban stormwater ponds: implications for regional biodiversity - James S. Sinclair; Lindsey S. Reisinger; Carrie R. Adams; Eban Bean; Alexander J. Reisinger; Basil V. Iannone (Urban Ecosystems, 2021)

Growth patterns of specialized reef fishes distributed across the Red Sea to Gulf of Aden - Joseph D. DiBattista; Brett M. Taylor; Jean-Paul A. Hobbs; Tane H. Sinclair-Taylor; Darren J. Coker; Elizabeth D. L. Trip; J. Howard Choat; Diego Lozano-Cortés; Nora M. Kandler; Michael L. Berumen (Environmental Biology of Fishes, 2021)

A robust machine learning framework to identify signatures for frailty: a nested case-control study in four aging European cohorts - David Gomez-Cabrero; Stefan Walter; Imad Abugessaisa; Rebeca Miñambres-Herraiz; Lucia Bernad Palomares; Lee Butcher; Jorge D. Erusalimsky; Francisco Jose Garcia-Garcia; José Carnicero; Timothy C. Hardman; Harald Mischak; Petra Zürbig; et al. (GeroScience, 2021)

Genomic sequencing highlights the diverse molecular causes of Perrault syndrome: a peroxisomal disorder (PEX6), metabolic disorders (CLPP, GGPS1), and mtDNA maintenance/translation disorders (LARS2, TFAM) - Elena J. Tucker; Rocio Rius; Sylvie Jaillard; Katrina Bell; Phillipa J. Lamont; André Travessa; Juliette Dupont; Lurdes Sampaio; Jérôme Dulon; Sandrine Vuillaumier-Barrot; Sandra Whalen; Arnaud Isapof; et al. (Human Genetics, 2020)

Blue Restoration – Building Confidence and Overcoming Barriers - Phoebe J. Stewart-Sinclair; Jemma Purandare; Elisa Bayraktarov; Nathan Waltham; Simon Reeves; John Statton; Elizabeth A. Sinclair; Benjamin M. Brown; Zoë I. Shribman; Catherine E. Lovelock (Frontiers in Marine Science, 2020)

How widespread are recruitment bottlenecks in fragmented populations of the savanna tree Banksia marginata (Proteaceae)? - Simon D. Heyes; Steve J. Sinclair; Susan E. Hoebee; John W. Morgan (Plant Ecology, 2020)

Regenerated trees in farmers’ fields increase soil carbon across the Sahel - J. Bayala; J. Sanou; H. R. Bazié; R. Coe; A. Kalinganire; F. L. Sinclair (Agroforestry Systems, 2020)

Does Proximity to Wetlands Matter? A Landscape-Level Analysis of the Influence of Local Wetlands on the Public’s Concern for Ecosystem Services and Conservation Involvement - Emily J. Wilkins; Wilson Sinclair; Holly M. Miller; Rudy M. Schuster (Wetlands, 2019)

Thermal limits of summer-collected Pardosa wolf spiders (Araneae: Lycosidae) from the Yukon Territory (Canada) and Greenland - Susan E. Anthony; Christopher M. Buddle; Toke T. Høye; Brent J. Sinclair (Polar Biology, 2019)

A Systematic Review of How Multiple Stressors From an Extreme Event Drove Ecosystem-Wide Loss of Resilience in an Iconic Seagrass Community - Gary A. Kendrick; Robert J. Nowicki; Ylva S. Olsen; Simone Strydom; Matthew W. Fraser; Elizabeth A. Sinclair; John Statton; Renae K. Hovey; Jordan A. Thomson; Derek A. Burkholder; Kathryn M. McMahon; Kieryn Kilminster; et al. (Frontiers in Marine Science, 2019)

The Australian National Rabbit Database: 50 yr of population monitoring of an invasive species - Emilie Roy‐Dufresne; Miguel Lurgi; Stuart C. Brown; Konstans Wells; Brian Cooke; Greg Mutze; David Peacock; Phill Cassey; Dave Berman; Barry W. Brook; Susan Campbell; Tarnya Cox; et al. (Ecology, 2019)
With ongoing introductions into Australia since the 1700s, the European rabbit ( Oryctolagus cuniculus ) has become one of the most widely distributed and abundant vertebrate pests, adversely impacting Australia's biodiversity and agroeconomy. To understand the population and range dynamics of the species and its impacts better, occurrence and abundance data have been collected by researchers and citizens from sites covering a broad spectrum of climatic and environmental conditions in Australia. The lack of a common and accessible repository for these data has, however, limited their use in determining important spatiotemporal drivers of the structure and dynamics of the geographical range of rabbits in Australia. To meet this need, we created the Australian National Rabbit Database, which combines more than 50 yr of historical and contemporary survey data collected from throughout the range of the species in Australia. The survey data, obtained from a suite of complementary monitoring methods, were combined with high‐resolution weather, climate, and environmental information, and an assessment of data quality. The database provides records of rabbit occurrence (689,265 records) and abundance (51,241 records, >120 distinct sites) suitable for identifying the spatiotemporal drivers of the rabbit's distribution and for determining spatial patterns of variation in its key life‐history traits, including maximum rates of population growth. Because all data are georeferenced and date stamped, they can be coupled with information from other databases and spatial layers to explore the potential effects of rabbit occurrence and abundance on Australia's native wildlife and agricultural production. The Australian National Rabbit Database is an important tool for understanding and managing the European rabbit in its invasive range and its effects on native biodiversity and agricultural production. It also provides a valuable resource for addressing questions related to the biology, success, and impacts of invasive species more generally. No copyright or proprietary restrictions are associated with the use of this data set other than citation of this Data Paper.

How does high DHA fish oil affect health? A systematic review of evidence - Samaneh Ghasemi Fard; Fenglei Wang; Andrew J. Sinclair; Glenn Elliott; Giovanni M. Turchini (Critical Reviews in Food Science and Nutrition, 2019)

Wide outcrossing provides functional connectivity for new and old Banksia populations within a fragmented landscape - Alison L. Ritchie; Rodney J. Dyer; Paul G. Nevill; Elizabeth A. Sinclair; Siegfried L. Krauss (Oecologia, 2019)

Enhancing maize productivity in agroforestry systems through managing competition: lessons from smallholders’ farms, Rift valley, Kenya - J. Nyaga; C. W. Muthuri; E. Barrios; I. Öborn; F. L. Sinclair (Agroforestry Systems, 2019)

Seeds in motion: Genetic assignment and hydrodynamic models demonstrate concordant patterns of seagrass dispersal - Elizabeth A. Sinclair; Leonardo Ruiz‐Montoya; Siegfried L. Krauss; Janet M. Anthony; Renae K. Hovey; Ryan J. Lowe; Gary A. Kendrick (Molecular Ecology, 2018)
Movement is fundamental to the ecology and evolutionary dynamics within species. Understanding movement through seed dispersal in the marine environment can be difficult due to the high spatial and temporal variability of ocean currents. We employed a mutually enriching approach of population genetic assignment procedures and dispersal predictions from a hydrodynamic model to overcome this difficulty and quantify the movement of dispersing floating fruit of the temperate seagrass Posidonia australis Hook.f. across coastal waters in south‐western Australia. Dispersing fruit cohorts were collected from the water surface over two consecutive years, and seeds were genotyped using microsatellite DNA markers. Likelihood‐based genetic assignment tests were used to infer the meadow of origin for seed cohorts and individuals. A three‐dimensional hydrodynamic model was coupled with a particle transport model to simulate the movement of fruit at the water surface. Floating fruit cohorts were mainly assigned genetically to the nearest meadow, but significant genetic differentiation between cohort and most likely meadow of origin suggested a mixed origin. This was confirmed by genetic assignment of individual seeds from the same cohort to multiple meadows. The hydrodynamic model predicted 60% of fruit dispersed within 20 km, but that fruit was physically capable of dispersing beyond the study region. Concordance between these two independent measures of dispersal provides insight into the role of physical transport for long distance dispersal of fruit and the consequences for spatial genetic structuring of seagrass meadows.

Probability of emerald ash borer impact for Canadian cities and North America: a mechanistic model - Kim Cuddington; Stephanie Sobek-Swant; Jill C. Crosthwaite; D. Barry Lyons; Brent J. Sinclair (Biological Invasions, 2018)

The limitations of some European healthcare databases for monitoring the effectiveness of pregnancy prevention programmes as risk minimisation measures - R. A. Charlton; V. Bettoli; H. J. Bos; A. Engeland; E. Garne; R. Gini; A. V. Hansen; L. T. W. de Jong-van den berg; S. Jordan; K. Klungsøyr; A. J. Neville; A. Pierini; et al. (European Journal of Clinical Pharmacology, 2018)

Breakdown in assortative mating leads to hybrid swarm in pygmy angelfishes - J. P. A. Hobbs; J. D. DiBattista; T. H. Sinclair-Taylor (Coral Reefs, 2018)

Spatial patterns of cryptobenthic coral-reef fishes in the Red Sea - Darren J. Coker; Joseph D. DiBattista; Tane H. Sinclair-Taylor; Michael L. Berumen (Coral Reefs, 2018)

International Trials of Vertical Flow Reactors for Coal Mine Water Treatment - Ivan Blanco; Devin J. Sapsford; Dave Trumm; James Pope; Natalie Kruse; Young-wook Cheong; Hamish McLauchlan; Eden Sinclair; Paul Weber; William Olds (Mine Water and the Environment, 2018)

A condition metric for Eucalyptus woodland derived from expert evaluations - Steve J. Sinclair; Matthew J. Bruce; Peter Griffioen; Amanda Dodd; Matthew D. White (Conservation Biology, 2018)
The evaluation of ecosystem quality is important for land‐management and land‐use planning. Evaluation is unavoidably subjective, and robust metrics must be based on consensus and the structured use of observations. We devised a transparent and repeatable process for building and testing ecosystem metrics based on expert data. We gathered quantitative evaluation data on the quality of hypothetical grassy woodland sites from experts. We used these data to train a model (an ensemble of 30 bagged regression trees) capable of predicting the perceived quality of similar hypothetical woodlands based on a set of 13 site variables as inputs (e.g., cover of shrubs, richness of native forbs). These variables can be measured at any site and the model implemented in a spreadsheet as a metric of woodland quality. We also investigated the number of experts required to produce an opinion data set sufficient for the construction of a metric. The model produced evaluations similar to those provided by experts, as shown by assessing the model's quality scores of expert‐evaluated test sites not used to train the model. We applied the metric to 13 woodland conservation reserves and asked managers of these sites to independently evaluate their quality. To assess metric performance, we compared the model's evaluation of site quality with the managers’ evaluations through multidimensional scaling. The metric performed relatively well, plotting close to the center of the space defined by the evaluators. Given the method provides data‐driven consensus and repeatability, which no single human evaluator can provide, we suggest it is a valuable tool for evaluating ecosystem quality in real‐world contexts. We believe our approach is applicable to any ecosystem.

Recovery following a marathon: a comparison of cold water immersion, whole body cryotherapy and a placebo control - Laura J. Wilson; Emma Cockburn; Katherine Paice; Scott Sinclair; Tanwir Faki; Frank A. Hills; Marcela B. Gondek; Alyssa Wood; Lygeri Dimitriou (European Journal of Applied Physiology, 2018)

Ancient chromosomal rearrangement associated with local adaptation of a postglacially colonized population of Atlantic Cod in the northwest Atlantic - Marion Sinclair‐Waters; Ian R. Bradbury; Corey J. Morris; Sigbjørn Lien; Matthew P. Kent; Paul Bentzen (Molecular Ecology, 2018)
Intraspecific diversity is central to the management and conservation of exploited species, yet knowledge of how this diversity is distributed and maintained in the genome of many marine species is lacking. Recent advances in genomic analyses allow for genome‐wide surveys of intraspecific diversity and offer new opportunities for exploring genomic patterns of divergence. Here, we analysed genome‐wide polymorphisms to measure genetic differentiation between an offshore migratory and a nonmigratory population and to define conservation units of Atlantic Cod ( Gadus morhua ) in coastal Labrador. A total of 141 individuals, collected from offshore sites and from a coastal site within Gilbert Bay, Labrador, were genotyped using an ~11k single nucleotide polymorphism array. Analyses of population structure revealed strong genetic differentiation between migratory offshore cod and nonmigratory Gilbert Bay cod. Genetic differentiation was elevated for loci within a chromosomal rearrangement found on linkage group 1 ( LG 1) that coincides with a previously found double inversion associated with migratory and nonmigratory ecotype divergence of cod in the northeast Atlantic. This inverted region includes several genes potentially associated with adaptation to differences in salinity and temperature, as well as influencing migratory behaviour. Our work provides evidence that a chromosomal rearrangement on LG 1 is associated with parallel patterns of divergence between migratory and nonmigratory ecotypes on both sides of the Atlantic Ocean.

Assessing the utility of eDNA as a tool to survey reef-fish communities in the Red Sea - Joseph D. DiBattista; Darren J. Coker; Tane H. Sinclair-Taylor; Michael Stat; Michael L. Berumen; Michael Bunce (Coral Reefs, 2017)

Comparative phylogeography of reef fishes from the Gulf of Aden to the Arabian Sea reveals two cryptic lineages - Joseph D. DiBattista; Michelle R. Gaither; Jean-Paul A. Hobbs; Pablo Saenz-Agudelo; Marek J. Piatek; Brian W. Bowen; Luiz A. Rocha; J. Howard Choat; Jennifer H. McIlwain; Mark A. Priest; Tane H. Sinclair-Taylor; Michael L. Berumen (Coral Reefs, 2017)

High adaptive variability and virus-driven selection on major histocompatibility complex (MHC) genes in invasive wild rabbits in Australia - Nina Schwensow; Camila J. Mazzoni; Elena Marmesat; Joerns Fickel; David Peacock; John Kovaliski; Ron Sinclair; Phillip Cassey; Brian Cooke; Simone Sommer (Biological Invasions, 2017)

Microbial changes linked to the accelerated degradation of the herbicide atrazine in a range of temperate soils - R. L. Yale; M. Sapp; C. J. Sinclair; J. W. B. Moir (Environmental Science and Pollution Research, 2017)

Hybridisation among groupers (genus Cephalopholis) at the eastern Indian Ocean suture zone: taxonomic and evolutionary implications - Samuel D. Payet; Jean-Paul A. Hobbs; Joseph D. DiBattista; Stephen J. Newman; Tane Sinclair-Taylor; Michael L. Berumen; Jennifer L. McIlwain (Coral Reefs, 2016)

Can we predict ectotherm responses to climate change using thermal performance curves and body temperatures? - Brent J. Sinclair; Katie E. Marshall; Mary A. Sewell; Danielle L. Levesque; Christopher S. Willett; Stine Slotsbo; Yunwei Dong; Christopher D. G. Harley; David J. Marshall; Brian S. Helmuth; Raymond B. Huey (Ecology Letters, 2016)
Thermal performance curves ( TPC s), which quantify how an ectotherm's body temperature ( T b ) affects its performance or fitness, are often used in an attempt to predict organismal responses to climate change. Here, we examine the key – but often biologically unreasonable – assumptions underlying this approach; for example, that physiology and thermal regimes are invariant over ontogeny, space and time, and also that TPC s are independent of previously experienced T b. We show how a critical consideration of these assumptions can lead to biologically useful hypotheses and experimental designs. For example, rather than assuming that TPC s are fixed during ontogeny, one can measure TPC s for each major life stage and incorporate these into stage‐specific ecological models to reveal the life stage most likely to be vulnerable to climate change. Our overall goal is to explicitly examine the assumptions underlying the integration of TPC s with T b , to develop a framework within which empiricists can place their work within these limitations, and to facilitate the application of thermal physiology to understanding the biological implications of climate change.

Thermal biology and immersion tolerance of the Beringian pseudoscorpion Wyochernes asiaticus - Susan E. Anthony; Christopher M. Buddle; Brent J. Sinclair (Polar Biology, 2016)

Testing the generality of above‐ground biomass allometry across plant functional types at the continent scale - Keryn I. Paul; Stephen H. Roxburgh; Jerome Chave; Jacqueline R. England; Ayalsew Zerihun; Alison Specht; Tom Lewis; Lauren T. Bennett; Thomas G. Baker; Mark A. Adams; Dan Huxtable; Kelvin D. Montagu; et al. (Global Change Biology, 2016)
Accurate ground‐based estimation of the carbon stored in terrestrial ecosystems is critical to quantifying the global carbon budget. Allometric models provide cost‐effective methods for biomass prediction. But do such models vary with ecoregion or plant functional type? We compiled 15 054 measurements of individual tree or shrub biomass from across Australia to examine the generality of allometric models for above‐ground biomass prediction. This provided a robust case study because Australia includes ecoregions ranging from arid shrublands to tropical rainforests, and has a rich history of biomass research, particularly in planted forests. Regardless of ecoregion, for five broad categories of plant functional type (shrubs; multistemmed trees; trees of the genus Eucalyptus and closely related genera; other trees of high wood density; and other trees of low wood density), relationships between biomass and stem diameter were generic. Simple power‐law models explained 84–95% of the variation in biomass, with little improvement in model performance when other plant variables (height, bole wood density), or site characteristics (climate, age, management) were included. Predictions of stand‐based biomass from allometric models of varying levels of generalization (species‐specific, plant functional type) were validated using whole‐plot harvest data from 17 contrasting stands (range: 9–356 Mg ha −1 ). Losses in efficiency of prediction were stand ‐level biomass prediction was 99%, with a mean absolute prediction error of only 13%. Hence, for cost‐effective prediction of biomass across a wide range of stands, we recommend use of generic allometric models based on plant functional types. Development of new species‐specific models is only warranted when gains in accuracy of stand‐based predictions are relatively high (e.g. high‐value monocultures).

Paradoxical acclimation responses in the thermal performance of insect immunity - Laura V. Ferguson; David E. Heinrichs; Brent J. Sinclair (Oecologia, 2016)

A review of contemporary patterns of endemism for shallow water reef fauna in the Red Sea - Joseph D. DiBattista; May B. Roberts; Jessica Bouwmeester; Brian W. Bowen; Darren J. Coker; Diego F. Lozano‐Cortés; J. Howard Choat; Michelle R. Gaither; Jean‐Paul A. Hobbs; Maha T. Khalil; Marc Kochzius; Robert F. Myers; et al. (Journal of Biogeography, 2016)
Aim The Red Sea is characterised by a unique fauna and historical periods of desiccation, hypersalinity and intermittent isolation. The origin and contemporary composition of reef‐associated taxa in this region can illuminate biogeographical principles about vicariance and the establishment (or local extirpation) of existing species. Here we aim to: (1) outline the distribution of shallow water fauna between the Red Sea and adjacent regions, (2) explore mechanisms for maintaining these distributions and (3) propose hypotheses to test these mechanisms. Location Red Sea, Gulf of Aden, Arabian Sea, Arabian Gulf and Indian Ocean. Methods Updated checklists for scleractinian corals, fishes and non‐coral invertebrates were used to determine species richness in the Red Sea and the rest of the Arabian Peninsula and assess levels of endemism. Fine‐scale diversity and abundance of reef fishes within the Red Sea were explored using ecological survey data. Results Within the Red Sea, we recorded 346 zooxanthellate and azooxanthellate scleractinian coral species of which 19 are endemic (5.5%). Currently 635 species of polychaetes, 211 echinoderms and 79 ascidians have been documented, with endemism rates of 12.6%, 8.1% and 16.5% respectively. A preliminary compilation of 231 species of crustaceans and 137 species of molluscs include 10.0% and 6.6% endemism respectively. We documented 1071 shallow fish species, with 12.9% endemic in the entire Red Sea and 14.1% endemic in the Red Sea and Gulf of Aden. Based on ecological survey data of endemic fishes, there were no major changes in species richness or abundance across 1100 km of Saudi Arabian coastline. Main conclusions The Red Sea biota appears resilient to major environmental fluctuations and is characterized by high rates of endemism with variable degrees of incursion into the Gulf of Aden. The nearby Omani and Arabian Gulfs also have variable environments and high levels of endemism, but these are not consistently distinct across taxa. The presence of physical barriers does not appear to explain species distributions, which are more likely determined by ecological plasticity and genetic diversity.

Diversity enhances carbon storage in tropical forests - L. Poorter; M. T. van der Sande; J. Thompson; E. J. M. M. Arets; A. Alarcón; J. Álvarez‐Sánchez; N. Ascarrunz; P. Balvanera; G. Barajas‐Guzmán; A. Boit; F. Bongers; F. A. Carvalho; et al. (Global Ecology and Biogeography, 2015)
Aim Tropical forests store 25% of global carbon and harbour 96% of the world's tree species, but it is not clear whether this high biodiversity matters for carbon storage. Few studies have teased apart the relative importance of forest attributes and environmental drivers for ecosystem functioning, and no such study exists for the tropics. Location Neotropics. Methods We relate aboveground biomass ( AGB ) to forest attributes (diversity and structure) and environmental drivers (annual rainfall and soil fertility) using data from 144,000 trees, 2050 forest plots and 59 forest sites. The sites span the complete latitudinal and climatic gradients in the lowland Neotropics, with rainfall ranging from 750 to 4350 mm year −1 . Relationships were analysed within forest sites at scales of 0.1 and 1 ha and across forest sites along large‐scale environmental gradients. We used a structural equation model to test the hypothesis that species richness, forest structural attributes and environmental drivers have independent, positive effects on AGB . Results Across sites, AGB was most strongly driven by rainfall, followed by average tree stem diameter and rarefied species richness, which all had positive effects on AGB . Our indicator of soil fertility (cation exchange capacity) had a negligible effect on AGB , perhaps because we used a global soil database. Taxonomic forest attributes (i.e. species richness, rarefied richness and Shannon diversity) had the strongest relationships with AGB at small spatial scales, where an additional species can still make a difference in terms of niche complementarity, while structural forest attributes (i.e. tree density and tree size) had strong relationships with AGB at all spatial scales. Main conclusions Biodiversity has an independent, positive effect on AGB and ecosystem functioning, not only in relatively simple temperate systems but also in structurally complex hyperdiverse tropical forests. Biodiversity conservation should therefore be a key component of the UN Reducing Emissions from Deforestation and Degradation strateg y.

A unified gene catalog for the laboratory mouse reference genome - Y. Zhu; J. E. Richardson; P. Hale; R. M. Baldarelli; D. J. Reed; J. M. Recla; R. Sinclair; T. B. K. Reddy; C. J. Bult (Mammalian Genome, 2015)

Isolation and characterisation of microsatellite loci for the ancient cephalopod, Nautilus pompilius - Rachel C. Williams; Deborah A. Dawson; Gavin J. Horsburgh; William Sinclair (Conservation Genetics Resources, 2015)

Loss of microbial diversity in soils is coincident with reductions in some specialized functions - Brajesh K. Singh; Christopher Quince; Catriona A. Macdonald; Amit Khachane; Nadine Thomas; Waleed Abu Al‐Soud; Søren J. Sørensen; Zhili He; Duncan White; Alex Sinclair; Bill Crooks; Jizhong Zhou; et al. (Environmental Microbiology, 2014)
Summary Loss of microbial diversity is considered a major threat because of its importance for ecosystem functions, but there is a lack of conclusive evidence that diversity itself is reduced under anthropogenic stress, and about the consequences of diversity loss. Heavy metals are one of the largest, widespread pollutant types globally, and these represent a significant environmental stressor for terrestrial microbial communities. Using combined metagenomics and functional assays, we show that the compositional and functional response of microbial communities to long‐term heavy metal stress results in a significant loss of diversity. Our results indicate that even at a moderate loss of diversity, some key specialized functions (carried out by specific groups) may be compromised. Together with previous work, our data suggest disproportionate impact of contamination on microbes that carry out specialized, but essential, ecosystem functions. Based on these findings, we propose a conceptual framework to explicitly consider diversity of functions and microbial functional groups to test the relationship between biodiversity and soil functions.

Is increased juvenile infection the key to recovery of wild rabbit populations from the impact of rabbit haemorrhagic disease? - G. J. Mutze; R. G. Sinclair; D. E. Peacock; L. Capucci; J. Kovaliski (European Journal of Wildlife Research, 2014)

Divergent transcriptional responses to low temperature among populations of alpine and lowland species of N ew Z ealand stick insects ( M icrarchus ) - Luke T. Dunning; Alice B. Dennis; Brent J. Sinclair; Richard D. Newcomb; Thomas R. Buckley (Molecular Ecology, 2014)
In widespread and genetically structured populations, temperature variation may lead to among‐population differentiation of thermal biology. The New Zealand stick insect genus Micrarchus contains four species that inhabit different thermal environments, two of which are geographically widespread. RNA ‐Seq and quantitative PCR were used to investigate the transcriptional responses to cold shock among lowland and alpine species to identify cold‐responsive transcripts that differ between the species and to determine whether there is intraspecific geographical variation in gene expression. We also used mitochondrial DNA , nuclear 28S ribosomal DNA and transcriptome‐wide SNP s to determine phylogeographic structure and the potential for differences in genetic backgrounds to contribute to variation in gene expression. RNA ‐Seq identified 2160 unigenes that were differentially expressed as a result of low‐temperature exposure across three populations from two species ( M. hystriculeus and M. nov. sp. 2), with a majority (68% ± 20%) being population specific. This extensive geographical variation is consistent across years and is likely a result of background genetic differences among populations caused by genetic drift and possibly local adaptation. Responses to cold shock shared among alpine M. nov. sp. 2 populations included the enrichment of cuticular structure‐associated transcripts, suggesting that cuticle modification may have accompanied colonization of low‐temperature alpine environments and the development of a more cold‐hardy phenotype.

Chemosensory and thermal cue responses in the sub-Antarctic moth Pringleophaga marioni: Do caterpillars choose Wandering Albatross nest proxies? - Tanya M. Haupt; Brent J. Sinclair; Steven L. Chown (Polar Biology, 2014)

Molecular epidemiology of R abbit H aemorrhagic D isease V irus in A ustralia: when one became many - John Kovaliski; Ron Sinclair; Greg Mutze; David Peacock; Tanja Strive; Joana Abrantes; Pedro J. Esteves; Edward C. Holmes (Molecular Ecology, 2014)
R abbit H aemorrhagic D isease V irus ( RHDV ) was introduced into A ustralia in 1995 as a biological control agent against the wild E uropean rabbit ( O ryctolagus cuniculus ). We evaluated its evolution over a 16‐year period (1995–2011) by examining 50 isolates collected throughout A ustralia, as well as the original inoculum strains. Phylogenetic analysis of capsid protein VP 60 sequences of the A ustralian isolates, compared with those sampled globally, revealed that they form a monophyletic group with the inoculum strains ( CAPM V‐351 and RHDV 351 INOC ). Strikingly, despite more than 3000 rereleases of RHDV 351 INOC since 1995, only a single viral lineage has sustained its transmission in the long‐term, indicative of a major competitive advantage. In addition, we find evidence for widespread viral gene flow, in which multiple lineages entered individual geographic locations, resulting in a marked turnover of viral lineages with time, as well as a continual increase in viral genetic diversity. The rate of RHDV evolution recorded in A ustralia −4.0 (3.3–4.7) × 10 −3 nucleotide substitutions per site per year – was higher than previously observed in RHDV , and evidence for adaptive evolution was obtained at two VP 60 residues. Finally, more intensive study of a single rabbit population (Turretfield) in S outh A ustralia provided no evidence for viral persistence between outbreaks, with genetic diversity instead generated by continual strain importation.

Site-specific water quality guidelines: 1. Derivation approaches based on physicochemical, ecotoxicological and ecological data - R. A. van Dam; C. L. Humphrey; A. J. Harford; A. Sinclair; D. R. Jones; S. Davies; A. W. Storey (Environmental Science and Pollution Research, 2014)

Conserving large populations of lions – the argument for fences has holes - S. Creel; M. S. Becker; S. M. Durant; J. M'Soka; W. Matandiko; A. J. Dickman; D. Christianson; E. Dröge; T. Mweetwa; N. Pettorelli; E. Rosenblatt; P. Schuette; et al. (Ecology Letters, 2013)
Packer et al . reported that fenced lion populations attain densities closer to carrying capacity than unfenced populations. However, fenced populations are often maintained above carrying capacity, and most are small. Many more lions are conserved per dollar invested in unfenced ecosystems, which avoid the ecological and economic costs of fencing.

Neuronal sirtuin1 mediates retinal vascular regeneration in oxygen-induced ischemic retinopathy - Jing Chen; Shaday Michan; Aimee M. Juan; Christian G. Hurst; Colman J. Hatton; Dorothy T. Pei; Jean-Sebastien Joyal; Lucy P. Evans; Zhenghao Cui; Andreas Stahl; Przemyslaw Sapieha; David A. Sinclair; et al. (Angiogenesis, 2013)

Asynchronous food‐web pathways could buffer the response of Serengeti predators to El Niño Southern Oscillation - A. R. E. Sinclair; Kristine L. Metzger; John M. Fryxell; Craig Packer; Andrea E. Byrom; Meggan E. Craft; Katie Hampson; Tiziana Lembo; Sarah M. Durant; Guy J. Forrester; John Bukombe; John Mchetto; et al. (Ecology, 2013)
Understanding how entire ecosystems maintain stability in the face of climatic and human disturbance is one of the most fundamental challenges in ecology. Theory suggests that a crucial factor determining the degree of ecosystem stability is simply the degree of synchrony with which different species in ecological food webs respond to environmental stochasticity. Ecosystems in which all food‐web pathways are affected similarly by external disturbance should amplify variability in top carnivore abundance over time due to population interactions, whereas ecosystems in which a large fraction of pathways are nonresponsive or even inversely responsive to external disturbance will have more constant levels of abundance at upper trophic levels. To test the mechanism underlying this hypothesis, we used over half a century of demographic data for multiple species in the Serengeti (Tanzania) ecosystem to measure the degree of synchrony to variation imposed by an external environmental driver, the El Niño Southern Oscillation (ENSO). ENSO effects were mediated largely via changes in dry‐season vs. wet‐season rainfall and consequent changes in vegetation availability, propagating via bottom‐up effects to higher levels of the Serengeti food web to influence herbivores, predators and parasites. Some species in the Serengeti food web responded to the influence of ENSO in opposite ways, whereas other species were insensitive to variation in ENSO. Although far from conclusive, our results suggest that a diffuse mixture of herbivore responses could help buffer top carnivores, such as Serengeti lions, from variability in climate. Future global climate changes that favor some pathways over others, however, could alter the effectiveness of such processes in the future.

Ontogenetic variation in cold tolerance plasticity in Drosophila: is the Bogert effect bogus? - Katherine A. Mitchell; Brent J. Sinclair; John S. Terblanche (The Science of Nature, 2013)

Planetary Stewardship in an Urbanizing World: Beyond City Limits - Sybil P. Seitzinger; Uno Svedin; Carole L. Crumley; Will Steffen; Saiful Arif Abdullah; Christine Alfsen; Wendy J. Broadgate; Frank Biermann; Ninad R. Bondre; John A. Dearing; Lisa Deutsch; Shobhakar Dhakal; et al. (Ambio, 2012)

Jumping on the Omega-3 Bandwagon: Distinguishing the Role of Long-Chain and Short-Chain Omega-3 Fatty Acids - Giovanni M. Turchini; Peter D. Nichols; Colin Barrow; Andrew J. Sinclair (Critical Reviews in Food Science and Nutrition, 2012)

Thermal biology of the alien ground beetle Merizodus soledadinus introduced to the Kerguelen Islands - L. Lalouette; C. M. Williams; M. Cottin; B. J. Sinclair; D. Renault (Polar Biology, 2012)

Biased Sex Ratios in Plants: Theory and Trends - Jordan P. Sinclair; J. Emlen; D. C. Freeman (The Botanical Review, 2012)

Erratum to: Threshold temperatures mediate the impact of reduced snow cover on overwintering freeze tolerant caterpillars - Katie E. Marshall; Brent J. Sinclair (The Science of Nature, 2012)

Threshold temperatures mediate the impact of reduced snow cover on overwintering freeze-tolerant caterpillars - Katie E. Marshall; Brent J. Sinclair (The Science of Nature, 2012)

The potential role of microRNAs in regulating gonadal sex differentiation in the chicken embryo - Andrew D. Cutting; Stephanie C. Bannister; Tim J. Doran; Andrew H. Sinclair; Mark V. L. Tizard; Craig A. Smith (Chromosome Research, 2012)

Could phenotypic plasticity limit an invasive species? Incomplete reversibility of mid-winter deacclimation in emerald ash borer - Stephanie Sobek-Swant; Jill C. Crosthwaite; D. Barry Lyons; Brent J. Sinclair (Biological Invasions, 2012)

Temporal and spatial variation in the δ15N and δ13C values of fish and squid from Alaskan waters - Carolyn M. Kurle; Elizabeth H. Sinclair; Ann E. Edwards; Carolyn J. Gudmundson (Marine Biology, 2011)

Microclimate impacts of passive warming methods in Antarctica: implications for climate change studies - Stef Bokhorst; Ad Huiskes; Peter Convey; Brent J. Sinclair; Marc Lebouvier; Bart Van de Vijver; Diana H. Wall (Polar Biology, 2011)

Exotic tree species displace indigenous ones on farms at intermediate altitudes around Mount Kenya - Katja Kehlenbeck; Roeland Kindt; Fergus L. Sinclair; Anthony J. Simons; Ramni Jamnadass (Agroforestry Systems, 2011)

Evaluating the protection of wildlife in parks: the case of African buffalo in Serengeti - K. L. Metzger; A. R. E. Sinclair; Ray Hilborn; J. Grant C. Hopcraft; Simon A. R. Mduma (Biodiversity and Conservation, 2010)

Characterisation of polymorphic microsatellite markers isolated from Drakaea glyptodon Fitz. (Orchidaceae) - J. M. Anthony; R. D. Phillips; E. A. Sinclair; K. W. Dixon (Conservation Genetics Resources, 2010)

Rapid and reliable determination of transgene zygosity in mice by multiplex ligation-dependent probe amplification - Amanda J. Notini; Ruili Li; Patrick S. Western; Andrew H. Sinclair; Stefan J. White (Transgenic Research, 2009)

Characterisation of polymorphic microsatellite markers in the widespread Australian seagrass, Posidonia australis Hook. f. (Posidoniaceae), with cross-amplification in the sympatric P. sinuosa - E. A. Sinclair; J. Anthony; G. T. Coupland; M. Waycott; M. D. Barrett; R. L. Barrett; M. L. Cambridge; M. J. Wallace; K. W. Dixon; S. L. Krauss; G. A. Kendrick (Conservation Genetics Resources, 2009)

DNA barcoding and the documentation of alien species establishment on sub-Antarctic Marion Island - Steven L. Chown; Brent J. Sinclair; Bettine Jansen van Vuuren (Polar Biology, 2008)

Ethical and welfare considerations when using cephalopods as experimental animals - N. A. Moltschaniwskyj; K. Hall; Marek R. Lipinski; J. E. A. R. Marian; M. Nishiguchi; M. Sakai; D. J. Shulman; B. Sinclair; D. L. Sinn; M. Staudinger; R. Van Gelderen; R. Villanueva; et al. (Reviews in Fish Biology and Fisheries, 2007)

Long‐Term Ecosystem Dynamics in the Serengeti: Lessons for Conservation - A.R.E. SINCLAIR; SIMON A.R. MDUMA; J. GRANT C. HOPCRAFT; JOHN M. FRYXELL; RAY HILBORN; SIMON THIRGOOD (Conservation Biology, 2007)
Data from long‐term ecological studies further understanding of ecosystem dynamics and can guide evidence‐based management. In a quasi‐natural experiment we examined long‐term monitoring data on different components of the Serengeti‐Mara Ecosystem to trace the effects of disturbances and thus to elucidate cause‐and‐effect connections between them. The long‐term data illustrated the role of food limitation in population regulation in mammals, particularly in migratory wildebeest and nonmigratory buffalo. Predation limited populations of smaller resident ungulates and small carnivores. Abiotic events, such as droughts and floods, created disturbances that affected survivorship of ungulates and birds. Such disturbances showed feedbacks between biotic and abiotic realms. Interactions between elephants and their food allowed savanna and grassland communities to co‐occur. With increased woodland vegetation, predators' capture of prey increased. Anthropogenic disturbances had direct (hunting) and indirect (transfer of disease to wildlife) effects. Slow and rapid changes and multiple ecosystem states became apparent only over several decades and involved events at different spatial scales. Conservation efforts should accommodate both infrequent and unpredictable events and long‐term trends. Management should plan on the time scale of those events and should not aim to maintain the status quo. Systems can be self‐regulating through food availability and predator‐prey interactions; thus, culling may not be required. Ecosystems can occur in multiple states; thus, there may be no a priori need to maintain one natural state. Finally, conservation efforts outside protected areas must distinguish between natural change and direct human‐induced change. Protected areas can act as ecological baselines in which human‐induced change is kept to a minimum

Do Exotic Vertebrates Structure the Biota of Australia? An Experimental Test in New South Wales - C. Davey; A. R. E. Sinclair; R. P. Pech; A. D. Arthur; C. J. Krebs; A. E. Newsome; D. Hik; R. Molsher; K. Allcock (Ecosystems, 2006)

Reduced inflammatory potential of peritoneal macrophages recruited in mice pretreated with a glycolipid synthesis inhibitor - H. C. Yohe; T. J. Kitzmiller; W. J. Bement; B. E. Dwyer; J. F. Sinclair (Inflammopharmacology, 2006)

Consequences of Transferring Three Sorghum Genes for Secondary Metabolite (Cyanogenic Glucoside) Biosynthesis to Grapevine Hairy Roots - T. K. Franks; K. S. Powell; S. Choimes; E. Marsh; P. Iocco; B. J. Sinclair; C. M. Ford; R. van Heeswijck (Transgenic Research, 2006)

Regulation of Harvest-induced Senescence in Broccoli (Brassica oleracea var. italica) by Cytokinin, Ethylene, and Sucrose - Nigel E. Gapper; Simon A. Coupe; Marian J. McKenzie; Ben K. Sinclair; Ross E. Lill; Paula E. Jameson (Journal of Plant Growth Regulation, 2005)

Perfluorinated Compounds in Aquatic Organisms at Various Trophic Levels in a Great Lakes Food Chain - Kurunthachalam Kannan; Lin Tao; Ewan Sinclair; Stephanie D Pastva; Dave J Jude; John P Giesy (Archives of Environmental Contamination and Toxicology, 2005)

Cold tolerance of Littorinidae from southern Africa: intertidal snails are not constrained to freeze tolerance - Brent J. Sinclair; David J. Marshall; Sarika Singh; Steven L. Chown (Journal of Comparative Physiology B, 2004)

What limits the Serengeti zebra population? - Sophie Grange; Patrick Duncan; Jean-Michel Gaillard; Anthony R. E. Sinclair; Peter J. P. Gogan; Craig Packer; Heribert Hofer; Marion East (Oecologia, 2004)

A global assessment using PCR techniques of mycorrhizal fungal populations colonising Tithonia diversifolia - R. A. Sharrock; F. L. Sinclair; C. Gliddon; I. M. Rao; E. Barrios; P. J. Mustonen; P. Smithson; D. L. Jones; D. L. Godbold (Mycorrhiza, 2004)

A basidiomycete isolated from the skeleton of Pocillopora damicornis (Scleractinia) selectively stimulates short-term survival of coral skeletogenic cells - I. J. Domart-Coulon; C. S. Sinclair; R. T. Hill; S. Tambutt; S. Puverel; G. K. Ostrander (Marine Biology, 2004)

Haemolymph osmolality and thermal hysteresis activity in 17 species of arthropods from sub-Antarctic Marion Island - Brent J. Sinclair; Steven L. Chown (Polar Biology, 2002)

Evolutionary relationships of the New Caledonian heterotrophic conifer, Parasitaxus usta (Podocarpaceae), inferred from chloroplast trn L-F intron/spacer and nuclear rDNA ITS2 sequences - W.T. Sinclair; R.R. Mill; M.F. Gardner; P. Woltz; T. Jaffré; J. Preston; M.L. Hollingsworth; A. Ponge; M. Möller (Plant Systematics and Evolution, 2002)

On-farm evaluation of the establishment of clonal rubber in multistrata agroforests in Jambi, Indonesia - S. E. Williams; M. van Noordwijk; E. Penot; J. R. Healey; F. L. Sinclair; G. Wibawa (Agroforestry Systems, 2001)

Essential genes in proximal 3L heterochromatin of Drosophila melanogaster - S. Schulze; D. A. R. Sinclair; E. Silva; K. A. Fitzpatrick; M. Singh; V. K. Lloyd; K. A. Morin; J. Kim; D. G. Holm; J. A. Kennison; B. M. Honda (Molecular Genetics and Genomics, 2001)

Molecular characterization of quinolinate phosphoribosyltransferase (QPRTase) in Nicotiana - Steven J. Sinclair; Kristina J. Murphy; Carlie D. Birch; John D. Hamill (Plant Molecular Biology, 2000)

The effects of traits of Bacillus megaterium onseed and root colonization and their correlation withthe suppression of Rhizoctonia root rot of soybean - X. Y. Zheng; J. B. Sinclair (BioControl, 2000)

Regional Patterns of Streamwater Acidity and Catchment Afforestation in Galloway, SW Scotland - Christoph B. Puhr; Daniel N. M. Donoghue; Alastair B. Stephen; David J. Tervet; Callum Sinclair (Water, Air, & Soil Pollution, 2000)

Sensitivity of a Standard Host Resistance Assay Using Streptococcus agalactiae for Assessing Exposure to Immunotoxicants in Wild Cotton Rats (Sigmodon hispidus) - L. C. Jones; R. L. Lochmiller; J. A. Sinclair; R. H. Morton (Archives of Environmental Contamination and Toxicology, 2000)

Sensitivity of a Standard Host Resistance Assay Using Streptococcus agalactiae for Assessing Exposure to Immunotoxicants in Wild Cotton Rats ( Sigmodon hispidus ) - L. C. Jones; R. L. Lochmiller; J. A. Sinclair; R. H. Morton (Archives of Environmental Contamination and Toxicology, 2000)

Zonal distribution and seasonal vertical migration of copepod assemblages in the Scotia Sea - A. Atkinson; J. D. Sinclair (Polar Biology, 2000)

Cod and haddock spawning on Georges Bank in relation to water residence times - F. H. Page; M. Sinclair; C. E. Naimie; J. W. Loder; R. J. Losier; P. L. Berrien; R. G. Lough (Fisheries Oceanography, 1999)
The seasonal and geographical patterns of spawning for Georges Bank cod ( Gadus morhua ) and haddock ( Melanogrammus aeglefinus ) are estimated using composite distributions of stage I eggs derived from the Marine Resources Monitoring, Assessment and Prediction (MARMAP) data set (1977–1987). The inferred mean spawning locations are compared with patterns in particle residence times derived from a three‐dimensional prognostic circulation model that estimates the tidal and seasonal mean circulation. The comparisons indicate that cod and haddock spawning occurs at times and locations characterized by model residence times in excess of 35 d. The results are discussed in the context of fish population regulation theory, particularly the member/vagrant hypothesis and the concept of abundance‐dependent vagrancy.

The postglacial history of Scots pine ( Pinus sylvestris L.) in western Europe: evidence from mitochondrial DNA variation - W. T. Sinclair; J. D. Morman; R. A. Ennos (Molecular Ecology, 1999)
The geographical structure of mitochondrial (mt)DNA variants (mitotypes) was investigated in 38 western European populations of Scots pine Pinus sylvestris using restriction fragment length polymorphism (RFLP) analysis of total DNA and a homologous cox1 probe. Three major mitotypes (designated a, b and d ) were detected. Within Spain all three major mitotypes were found, gene diversity was high, H T = 0.586, and this diversity was distributed predominantly among rather than within populations ( F ST(M) = 0.813 for the seven Spanish populations). Mitotype d was present only in the most southerly population from the Sierra Nevada . Elsewhere in Europe, populations showed little or no mtDNA diversity within regions, but there were marked differences between regions. Italian populations were fixed for mitotype b ; populations from northern France, Germany, Poland, Russia and southern Sweden were fixed for mitotype a ; while populations in northern Fennoscandia were fixed for mitotype b . The isolated Scottish populations were predominantly of mitotype a , but mitotype b was present in three of the 20 populations scored. In Scotland, UK gene diversity ( H T = 0.120) and genetic differentiation among populations ( F ST(M) = 0.37) was much lower than in Spain. When interpreted in the light of complementary data from pollen analysis and nuclear genetic markers, the results suggest that present‐day populations of P. sylvestris in western Europe have been derived from at least three different sources after glaciation.

Sensitivity of Wild Cotton Rats ( Sigmodon hispidus ) to the Immunotoxic Effects of Low-Level Arsenic Exposure - M. Savabieasfahani; R. L. Lochmiller; D. P. Rafferty; J. A. Sinclair (Archives of Environmental Contamination and Toxicology, 1998)

Calcium in gravitropism. A re-examination - William Sinclair; Anthony J. Trewavas (Planta, 1997)

Organochlorines and reproductive success of birds in orchard and non-orchard areas of central British Columbia, Canada, 1990?91 - J. E. Elliott; P. A. Martin; T. W. Arnold; P. H. Sinclair (Archives of Environmental Contamination and Toxicology, 1994)

Characterization of an antigenic site on glycoprotein 13 (gC) of equid herpesvirus type-1 - R. Sinclair; B. J. Moult; J. A. Mumford (Archives of Virology, 1993)

New Publications - J. B. Sinclair; Ken Pegg; A. C. Hayward (Australasian Plant Pathology, 1981)

“Biology and Pathology of Macrophimina phaseolina - O. D. Dhingra; J. B. Sinclair (Australasian Plant Pathology, 1978)

“An annoted bibliography of chickpea diseases 191 5-1 976” - Y. L. Nene; A. Mengitsu; J. B. Sinclair; D. J. Royse (Australasian Plant Pathology, 1978)